Strategic decision-making in presidential nominations : when and why party elites decide to support a candidate - Whitby, Kenny J., 1953- (State University of New York Press, 2014)
"Evaluates the how democratic presidential nominations are, using the historic race between Senators Obama and Clinton as a test case"--Provided by publisher